A critical ethnographic study of report writing as a literacy practice by automotive engineers - Harran, Marcelle (Rhodes University, Faculty of Education, Department of Education, 2007)
This study describes the social practices involved in the situated activity of report writing in an engineering automotive discourse community in South Africa. In particular, the study focuses on the subjectivity of predominantly English Second Language (ESL) engineers writing reports by determining what literacy means to them and what meanings they give to dominant literacy practices in report writing, especially feedback in text production. In the South African engineering workplace, because of the diversity and complexity of language and identity issues, the appropriation of the required literacy skills tends to be multifaceted. This context is made more complex as English is the business language upon which engineering is based with engineering competence often related to English proficiency. Therefore, the study is located within the understanding that literacy is always situated within specific discoursal practices whose ideologies, beliefs, power relations, values and identities are manifested rhetorically. The basis for this critical theory of literacy is the assertion that literacy is a social practice which involves not only observable units of behaviour but values, attitudes, feelings and social relationships. As the institution's socio-cultural context in the form of embedded historical and institutional forces impact on writer identity and writing practices or ways of doing report writing, notions of writing as a transparent and autonomous system are also challenged. As critical ethnography is concerned with multiple perspectives, it was selected as the preferred methodology and critical realism to derive definitions of truth and validity. Critical ethnography explores cultural orientations of local practice contexts and incorporates multiple understandings providing a holistic understanding of the complexity of writing practices. As human experience can only be known under particular descriptions, usually in terms of available discourses such as language, writing and rhetoric, the dominant practices emerging in response to the report acceptance event are explored, especially that of supervisor feedback practices as they causally impact on report-writing practices during the practice of report acceptance. Although critical realism does not necessarily demonstrate successful causal explanations, it does look for substantial relations within wider contexts to illuminate part-whole relationships. Therefore, an attempt is made to find representativeness or fit with situated engineering literacy practices and wider and changing literacy contexts, especially the impact of Higher Education and world Englishes as well as the expanding influence of technological and digital systems on report-writing practices.
Keywords: English language -- Written English -- South Africa; Written communication -- South Africa; Literacy -- Social aspects -- South Africa; Engineers -- Language -- South Africa; Communication in engineering -- South Africa